Innate immunity in tumors: roles and therapeutic targets - Leng, Songze; Ren, Yuyue; Tian, Yaoyao; Zhao, Weiwei; Mou, Yue; Chen, Xingyu; Zhou, Hong; Wang, Wei (Frontiers in Immunology, 2025)
Innate immune cells and pathways are central to shaping the tumor microenvironment (TME), where they influence tumor growth, metastasis, and responsiveness to immunotherapy. Although research on innate immunity in cancer has expanded considerably, the mechanisms driving immune dysfunction remain incompletely understood. This review summarizes current knowledge on the functional states of innate immune cells within the TME and highlights how metabolic reprogramming contributes to immune suppression and tumor progression. We further discuss recent advances in therapeutic strategies targeting innate immune pathways, emphasizing their translational potential. Importantly, we also examine unresolved controversies and knowledge gaps across innate immune cells, metabolic networks, and innate immune factors such as complement and cytokines, outlining key challenges for clinical translation. By linking mechanistic insights with emerging interventions and identifying future directions, this review provides a framework for integrating innate immunity into next-generation cancer treatment.